PEMILIHAN NASABAH PENERIMA HADIAH DOORPRIZE MENGUNAKAN METODE PROMETHEE (STUDI KASUS BANK SYARIAH MANDIRI KANTOR CABANG PEMATANGSIANTAR) - Lisa Andrianti Opusunggu; Muhammad Ilham; Putri Ayu Indah Sari; Muhammad Ridwan Lubis; Solikhun Solikhun (LPPM STMIK STIKOM Indonesia, 2019)
Doorprize is a gift given by the Bank Syariah Mandiri Brands Office Pematangsiantar for free through a lottery because of the amount of nominal value of saving for one month and the transactions made both in payment of shopping and so on and also a sign of memories in an event. A Doorprize wiil be highly anticipated by somenone because sometimes the Doorprize is very large. Therefore, here the author chooses the Promethee method to determine the selection of Doorprize. So here is the aim of attracting balances, savings and other transaction.